PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT UNTUK MENINGKATKAN KEAKTIFAN BELAJAR SISWA PADA MATEMATIKA [IMPLEMENTATION OF THE COOPERATIVE LEARNING MODEL TYPE TEAMS GAMES TOURNAMENT TO IMPROVE STUDENTS’ LEARNING ACTIVITIES IN MATHEMATICS] - Bernardinus Dickson Carnegie Maloring; Asihlya Sandu; Robert Harry Soesanto; Jacob S Seleky (Universitas Pelita Harapan, 2020)
Based on observations of a grade 10 social studies-track 2 class, students appeared less active in learning. Many students in the class looked sleepy, were too embarrassed to ask questions, did not want to join in discussions with their friends, and were too lazy to do the tasks. This research aims to understand whether the Team Game Tournament (TGT) method can increase the activeness of students. The method of Classroom Action Research is the model Kemmis and McTaggart administered in two cycles. The research was done at a school in Makassar with 25 students from the grade 10 social studies-track 2 as research subjects. The data were collected using mentor observation sheets, students' questionnaires and reflection journals. The results of the analysis show that the students’ activeness in participation, students’ activeness in sharing opinions, and students’ activeness in listening and discussing have reached the standard of success and received a